Visual Adaptation Of Wayang Characters In Teguh Santosa’s Comic Art - Mohammad Isa Pramana Koesoemadinata (Institut Seni Indonesia Denpasar, 2018)
Wayang tradition with its Indian epics of Mahabharata and Ramayana adaptations is the Indonesian high culture acknowledged by UNESCO since 2003. Its stories and characterizations has become philosophical, moral ethics and character learning for the young generations. Those Indian epics have acculturated in every aspect of theatrical and visual arts which are presented in shadow puppet theatre. As the part of traditional visual art, the visual aspect of wayang puppet consists of particular and systematic patterns (systems), in relation to role and characterization. In accordance with technological development, the famous epics of wayang are presented through popular modern media such as comic. Comic art is a popular media which adored by children and teenagers due to its visual narrative appeal. Many Indonesian comic artists such as Ardisoma, R.A. Kosasih, Oerip and Teguh Santosa adopt wayang epics through their own styles. The later artist, Teguh Santosa with his unique visual styles, has contributed color in wayang genre of Indonesian comic. Mostly, parallelities between Teguh’s style and the visual system of wayang role and characterization are detected. This paper discusses how visual adaptations of protagonists and antagonists wayang characters into Mahabharata comic series created by Teguh take place. Those visual adaptations are compared with the visual system of Javanese wayang puppetry, analyzed qualitative-descriptively with Sociology of Art and Aesthetical Morphology (Art Critic) methods. The results indicate that Teguh comprehends the essence of Javanese wayang’s visual aspect, since he adapted it with his own style yet still retains the visual system of Javanese wayang role and characterization.Tradisi Perwayangan dengan adaptasi wiracarita Mahabharata dan Ramayana adalah budaya adiluhung Indonesia yang sudah diakui UNESCO sejak 2003. Kisah-kisah dan penokohannya dijadikan model pembelajaran filsafat, etika moral dan karakter kepada generasi muda. Kisah-kisah tersebut mengalami akulturasi dalam berbagai aspek seni pertunjukan dan senirupa, di mana mereka disajikan dalam pertunjukan wayang kulit. Rupa boneka wayang kulit sendiri sebagai artefak senirupa tradisi memiliki pola yang khas dan sistematis, terkait dengan aspek perwatakan dan raut peranan tokoh. Seiring perkembangan zaman, kisah-kisah terkenal Perwayangan seperti Mahabharata dan Ramayana disajikan melalui media modern populer seperti komik. Komik adalah media populer yang lazim digemari anak-anak dan remaja karena memiliki daya tarik berupa narasi visual. Banyak komikus Indonesia mengadaptasi kisah perwayangan dengan gayanya masing-masing, seperti Ardisoma, R.A. Kosasih, Oerip, termasuk Teguh Santosa. Teguh Santosa (1942 – 2000) dengan kekhasan gaya visualnya telah memberikan nuansa tersendiri dalam komik indonesia khususnya genre perwayangan. Terlebih lagi penulis mendapati adanya kesejajaran pola visual antara gaya Teguh dengan pola rupa wayang kulit terkait perwatakan atau raut peranan tokoh. Tulisan ini mengkaji bagaimana adaptasi visual pada beberapa tokoh wayang protagonis dan antagonis dalam seri komik Mahabharata (1983-1985, 1986-1987) sisipan majalah Ananda dan terbitan Misurind karya Teguh Santosa. Adaptasi visual tersebut diperbandingkan dengan pola visual wayang kulit Jawa, dianalisis secara kualitatif-deskriptif, dengan pendekatan Sosiologi Seni dan Morfologi Estetik (Kritik Seni). Hasil analisis menunjukkan bahwa Teguh sebagai komikus memang memahami betul esensi rupa wayang Jawa, karena ia mengadaptasinya dalam komik dengan gaya visualnya sendiri namun tetap mempertahankan pola visual raut peranan dari wayang kulit Jawa.